СМЕНА ПАРАДИГМЫ РЕГИОНАЛЬНОЙ ПОЛИТИКИ В XXI ВЕКЕ (ЗАРУБЕЖНЫЙ ОПЫТ И РЕКОМЕНДАЦИИ ДЛЯ КАЗАХСТАНА) - N. K. Nurlanova (Экономика: стратегия и практика, 2019)
The purpose of this research is to investigate the evolution of regional policy, models existing theory and practice, mechanisms and approaches for spatial development, substantiation of the most acceptable paradigm of the formation and implementation of regional policies for Kazakhstan in the 21st century.In this study have used the scientific research methods: systematic approach, logical analysis, comparisons, analogies, abstractions, identifications, typologies, generalization, scenario modeling. Further, it have studied the main priorities and mechanisms for the implementation of regional policies in foreign countries and changes of their trends over more than half century. It have related the main models of regional policy (polarized selective, leveling selective, stimulating, restraining), applied in different periods, features of their characteristics, tools and implementation methods.It have concluded that the regional policies of many countries again began to focus on leveling regional disparities under the influence of the global challenges of the 21st century. The main instruments for its implementation have changed and direct state support of depressed regions have given way to methods of stimulating growth.It have justified that it is need to develop a new regional policy in Kazakhstan, which provides: firstly, the use of internal resources; secondly, the formation of new “growth points”; thirdly, the smoothing of social and economic disproportions of the territories according to the principle of inclusive development.It have given the recommendations on the development of comprehensive program for the long-term development of depressed regions in Kazakhstan, and have substantiated the algorithm for its implementation.